STARS IN THE ORIGIN AND EVOLUTION OF SPECIES - Rao, Y. V. Subba (International Journal of Research -GRANTHAALAYAH, 2021)
The proposed hypothesis of ‘Stars in the Origin and Evolution of Species’ is based on the principle underlying in ‘Jyotish’, one of the six Vedāngas and ancillary of most ancient Vedas of Hinduism. The principle of interaction of electromagnetic force with inorganic chemistry available to us in the universe defines life as an emergent property of matter and as the most plausible hypothesis for explaining the extra-terrestrial origin of species. The current hypothesis of evolution explains the critical milestones in the development of advanced life on Earth during the Cambrian explosion and the complexity of life when humans appeared on earth endowed with a brain of extraordinary intellectual capacities and capabilities which is far more complex than the animal brain and its development in stages is also observed as a plausible mechanism in tune with the phases of elements given out by the stars during their life cycles.